The influence of digitalisation on procurement efficiency - Florian Bauer; Martin Göbl (Journal of Applied Leadership and Management, 2019)
Research question: Are there any benefits of digitalisation on the efficiency in procurement and how does digitalisation influences efficiency in procurement? Methods: After creating a questionnaire, a survey via internet was conducted through various procurement departments of companies about digitalisation in procurement and its relation to efficiency. With the answers, the influence of digitalisation on efficiency was analysed to understand how and if digitalisation has an impact on procurement. Results: The analysis shows that procurement departments with a higher degree of digitalisation are benefiting of higher efficiency and the reduction of administrative and manual tasks. Especially procurement departments with integrated and universally connected systems have even a bigger benefit on efficiency. Also, the results of the analysis show that the age of the interviewees doesn't influences the expectations on digitalisation and has no any impact on the efficiency through digitalisation.
Keywords: 650